2011
DOI: 10.1016/j.tice.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

IGFR-I expression and structural analysis of the hard palatine mucosa in an ethanol-drinking rat strain (UChA and UChB)

Abstract: The study analyzed the effects of chronic alcohol ingestion on the ultrastructure of the lining epithelium of the hard palatine mucosa of rats UChA and UChB (lines with voluntary alcohol consumption) in order to contribute to the understanding of the consequences of alcohol abuse for the morphology of the digestive system. Thirty female adult animals aged 120 days were divided into three experimental groups. (1) Ten UChA rats (genetically low ethanol consumer) with voluntary intake of 10% v/v (5.45 g/kg/day) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Although a large number of studies have evaluated the effects of alcohol intake on the organism (Abdelaziz & Osman, ; Adewole, ; Ahmed, Ebnoof, Hussein, & Gbreel, ; Boffetta, Mashberg, Winkelmann, & Garfinkel, ; Bor‐Caymaz, Bor, Tobey, Abdulnour‐Nakhoul, & Orlando, ; Brugere, Guenel, Leclerc, & Rodriguez, ; Howie et al., ; Maier et al., ; Martinez, De Oliveria et al., ; Ogden, Wight, & Cowpe, ; Pavanello, Prado, Balducci, Brandão, & Almeida, ; Reis, do Espírito Santo, Andrade, & Sadigursky, ; Shivappa et al., ; Slomiany, Piotrowski, & Slomiany, ; Slomiany et al., ,c; Varoni et al., ) and some have found morphological changes in the mucosa (Born et al., ; Maier et al., ; Martinez, Milton et al., ; Mascrès et al., ; Valentine et al., ), the comparison of the findings to those of the present study is hindered by the lack of methodological standardization, with differences in the species of animal employed, the diet of the animal, concentration of alcohol, type of administration (oral pathway or topical), duration and form of administration. Due to the short evaluation periods in the present study, no signs of metaplasia or neoplasia were found.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of studies have evaluated the effects of alcohol intake on the organism (Abdelaziz & Osman, ; Adewole, ; Ahmed, Ebnoof, Hussein, & Gbreel, ; Boffetta, Mashberg, Winkelmann, & Garfinkel, ; Bor‐Caymaz, Bor, Tobey, Abdulnour‐Nakhoul, & Orlando, ; Brugere, Guenel, Leclerc, & Rodriguez, ; Howie et al., ; Maier et al., ; Martinez, De Oliveria et al., ; Ogden, Wight, & Cowpe, ; Pavanello, Prado, Balducci, Brandão, & Almeida, ; Reis, do Espírito Santo, Andrade, & Sadigursky, ; Shivappa et al., ; Slomiany, Piotrowski, & Slomiany, ; Slomiany et al., ,c; Varoni et al., ) and some have found morphological changes in the mucosa (Born et al., ; Maier et al., ; Martinez, Milton et al., ; Mascrès et al., ; Valentine et al., ), the comparison of the findings to those of the present study is hindered by the lack of methodological standardization, with differences in the species of animal employed, the diet of the animal, concentration of alcohol, type of administration (oral pathway or topical), duration and form of administration. Due to the short evaluation periods in the present study, no signs of metaplasia or neoplasia were found.…”
Section: Discussionmentioning
confidence: 99%